2023
DOI: 10.3390/medicina59020236
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Assisted Total Knee Arthroplasty Utilizing NAVIO, CORI Imageless Systems and Manual TKA Accurately Restore Femoral Rotational Alignment and Yield Satisfactory Clinical Outcomes: A Randomized Controlled Trial

Abstract: Background and objectives: The introduction of novel techniques in total knee arthroplasty (TKA) aiming to enhance outcomes and satisfaction of the procedure is constantly ongoing. In order to evidence a priority of one, we have conducted a randomized controlled trial with the aim of comparing patient-reported functional outcomes, radiographic outcomes and intraoperative measures between imageless (NAVIO and CORI), robotic-assisted (ra)- TKA (ra-TKA) and manual TKA (mTKA) for primary knee osteoarthritis (KOA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“… 8 indicated that RA-TKA can also improve accuracy and precision in final polyethylene insert thickness compared to conventional techniques. Similarly, in this study and our previous studies we found the statistically significant association between RA-TKA and better alignment 27 . However, it still has been controversial whether to recommend RA-TKA in current clinical practice because some previous studies demonstrated that RA-TKA seemed to have similar clinical outcomes with conventional TKA but much higher cost 28 , 29 .…”
Section: Discussionsupporting
confidence: 91%
“… 8 indicated that RA-TKA can also improve accuracy and precision in final polyethylene insert thickness compared to conventional techniques. Similarly, in this study and our previous studies we found the statistically significant association between RA-TKA and better alignment 27 . However, it still has been controversial whether to recommend RA-TKA in current clinical practice because some previous studies demonstrated that RA-TKA seemed to have similar clinical outcomes with conventional TKA but much higher cost 28 , 29 .…”
Section: Discussionsupporting
confidence: 91%
“…At present, treatment for knee osteoarthritis (KOA) is divided into non-surgical and surgical therapy. Surgical interventions address symptoms by removing excess synovial tissue and osteophytes, repairing ligaments, and replacing roughened cartilage surfaces [26,27] . Non-surgical options include both regenerative and non-regenerative therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Cutting, coagulation, and suturing end effectors are controlled by surgeons. In February 2022 the company Smith & Nephew announced the launch of the CORI robotic-assisted surgical system for knee arthroplasty [ 46 ]. The compact robotic solution includes 3-D intraoperative imaging with a robotic milling tool.…”
Section: Methodsmentioning
confidence: 99%